Library Web sites : creating online collections and services - Wilson, A. Paula (American Library Association, 2004)
Information-hungry consumers have become accustomed to flashy commercial web sites, the lightning speed of major search engines, and the seemingly endless array of "content" at sites like BN.com or Amazon.com. Libraries committed to delivering online content and services in this frenzied environment need the authoritative guidance and practical know-how available in Library Web Sites. This patron-centered step-by-step guide is the foundation for creating either basic or advanced online library services and integrating all aspects of library activities in the virtual world. Beginning with a checklist of elements essential to a library web site, it further explains how to: Manage content using database-backed Web pages Brand the library's marketing and promote services online Integrate external contentlicensed databases, library catalog and e-booksonto the site Conduct readers' advisory services online Keep the site fresh and updated using the editorial calendar tool Archive online resources Public and academic librarians, technology specialists, and all those front line staff responsible for creating, designing, and updating the library's web site will find an all-encompassing user-friendly guide designed to help them make the library's vast resources accessible online